Solar PV System Design for Enhancing Sustainability in SWRO Desalination: The Deir El‑Balah Case Study - Mizyed, Amjad (New Energy Exploitation and Application, 2025)
The Gaza Strip faces a dual challenge of severe freshwater scarcity and chronic electricity shortages, constraining the operation of critical infrastructure such as seawater desalination plants. This study investigates the design and feasibility of integrating a solar photovoltaic (PV) system into the Deir El-Balah seawater reverse osmosis (SWRO) desalination plant to enhance sustainability, reduce dependency on external electricity supplies, and minimize environmental impacts. Using the Helioscope simulation tool, both on-grid and off-grid scenarios were evaluated to assess system performance under local solar conditions. The optimized design requires 2,663 Canadian Solar HiKu CS3W-415P modules with Enphase M250 inverters, yielding a total installed capacity of 1.11 MWp and an AC output of 639 kW. Modules were allocated across rooftop structures and ground-mounted plots to maximize land-use efficiency. The system can meet the plant’s daily demand of approximately 1,100 kWh, thereby reducing reliance on fossil fuels and mitigating greenhouse gas emissions. Beyond technical performance, the integration of solar PV offers strategic benefits, including cost savings, improved energy security, and alignment with global sustainability agendas. The findings highlight the potential of renewable-powered desalination to contribute to Sustainable Development Goals (SDGs 6, 7, and 13) while advancing resilience and energy–water security in resource-constrained regions.